Design of Goods and Services in Developing Business - Siti Julaeha, Lia; Yustriana (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
Products and services presented to the public are the basis of the company's existence. Because the needs and wants of the market are always changing, it is necessary to adjust and develop goods and services. This paper aims to explain the design of products and services in developing a business conceptually and accompanied by several applications in the company. This paper is a descriptive qualitative literature review that aims to analyze the design strategy of goods and services in developing a business. This paper uses the method of documentation from books, journals, and websites to collect data which will then analyze deductively, inductively, and comparatively. The finding in this paper is that companies are required to consistently have the ability to come up with new products to be designed, developed, and marketed. In general, there are four product life cycles, namely the introduction stage, the development stage, the maturity stage, and the decline stage. Product development has several steps, including product selection, initial design, prototype development, testing, and final design. In service design, management needs to know consumers' expectations, and the strategy applied to service design defines the accuracy of what goods need to be used in service companies. Meanwhile, in a goods company, product design is made to make the product more attractive and unique to increase the selling value and develop the business. The similarity of this paper with others is the discussion of the design of goods and services, while the difference is that this paper is a dissertation on the application of goods and services in a company